If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 9 = n + -2 Reorder the terms: 9 + 3n = n + -2 Reorder the terms: 9 + 3n = -2 + n Solving 9 + 3n = -2 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 9 + 3n + -1n = -2 + n + -1n Combine like terms: 3n + -1n = 2n 9 + 2n = -2 + n + -1n Combine like terms: n + -1n = 0 9 + 2n = -2 + 0 9 + 2n = -2 Add '-9' to each side of the equation. 9 + -9 + 2n = -2 + -9 Combine like terms: 9 + -9 = 0 0 + 2n = -2 + -9 2n = -2 + -9 Combine like terms: -2 + -9 = -11 2n = -11 Divide each side by '2'. n = -5.5 Simplifying n = -5.5
| -3(6x-5)+6x=-27-5x | | -9(b-5)=54 | | 50=3x+23 | | 12-n=-3(4-4n)-2 | | 4x+9x-54=36-5x | | 2*4s-16-5s=-5 | | ((x^2)+4)dy+(e^2)dx=0 | | 16=10n | | 9-19+8b=4b+3+2b+2b | | 3(-x+2)=6x+15 | | lnx+lnx=-2 | | 3(x+4)+6x=-24 | | 3x+2-4y=6 | | 5x-(6+4x)=-3x-18 | | ((x^2)+4)dy+(e^2y)dx=0 | | 5-7x=11+7x | | 4=2(x-3)-7x | | f(-3)=x^2-2 | | 10v+90=36v | | -3(a-6)=6-5a | | 3a+4(1+3a)=a-24 | | 39=5x+4(x+3) | | m=-f+5qf | | 18+6x=5(2x+6) | | -2x+4=2(4x-3)-3(-8+4) | | 18/2=81/x | | 3x^2+10xy+3y^2=9 | | 2x+2=nx-3forn | | -4+(-8)=x | | 3x-4+2x=3[2x-5(x-2)]+4 | | 15h+2=8h-19 | | -12+4n=-6(3n+2) |